Synthesis of Vinegar Acid with Raja Uli Banana Peel (Musa paradiaca) by Adding Bagasse Water (Saccharum officinarum) - Nurhasanah Nurhasanah; Zona Octarya (Indonesian Journal of Chemical Science and Technology (IJCST), 2018)
The large amount of banana peel waste that increased soil acidity and caused environmental pollution. Bagasse water was used to provide additional sugar besides using Raja Uli banana peel due to the use of sugar is less economical This study is aimed at making vinegar acid with Raja Uli banana peel by adding bagasse water as the weak electrolyte solution on electrolyte and non-electrolyte practice . The optimization was done at the time used for fermentation by varying the time 1, 2, 3, and 4 days in each fermentation step. For testing vinegar acid, FeCl3 and H2SO4 as the qualitative test and alkalimetric titration were used as the quantitative test. The results showed that the third day was the optimum time to produce alcohol content with an average percentage of 2.5% and optimum acetic acid of 0.063 g / 100 mL.